2008
DOI: 10.1038/nature06947
|View full text |Cite|
|
Sign up to set email alerts
|

Domain organization of human chromosomes revealed by mapping of nuclear lamina interactions

Abstract: The architecture of human chromosomes in interphase nuclei is still largely unknown. Microscopy studies have indicated that specific regions of chromosomes are located in close proximity to the nuclear lamina (NL). This has led to the idea that certain genomic elements may be attached to the NL, which may contribute to the spatial organization of chromosomes inside the nucleus. However, sequences in the human genome that interact with the NL in vivo have not been identified. Here we construct a high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

127
2,009
2
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,734 publications
(2,149 citation statements)
references
References 35 publications
127
2,009
2
11
Order By: Relevance
“…Consistent with previous reports, nuclei in old livers are distorted and of irregular shape (Figure 1a, bottom panel), and aged hepatocytes accumulate lipids (Figure 1b, bottom panel, lipid droplets indicated by arrows). Lamina‐associated domains lack active histone marks and contain repressive H3K9me2 and H3K9me3 modifications (Guelen et al., 2008; Sadaie et al., 2013). Lamina‐associated domains present in both young and old livers, enriched for chromatin marks H3K9me2 and H3K9me3, are shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous reports, nuclei in old livers are distorted and of irregular shape (Figure 1a, bottom panel), and aged hepatocytes accumulate lipids (Figure 1b, bottom panel, lipid droplets indicated by arrows). Lamina‐associated domains lack active histone marks and contain repressive H3K9me2 and H3K9me3 modifications (Guelen et al., 2008; Sadaie et al., 2013). Lamina‐associated domains present in both young and old livers, enriched for chromatin marks H3K9me2 and H3K9me3, are shown in Figure 1c.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, LMNA mutations lead to partial lipodystrophy, a condition associated with insulin‐resistant diabetes, hypertriglyceridemia, and hepatic steatosis (Shackleton et al., 2000). Multiple enzymes modulating covalent modifications to lysine 9 of histone 3 (H3K9), the mark associated with heterochromatin in lamina‐associated domains (Guelen et al., 2008), have been linked to fatty liver, hyperlipidemia, diabetes, and obesity (Picard et al., 2002; Sun et al., 2012; Tateishi, Okada, Kallin & Zhang, 2009; Villeneuve et al., 2008; Wang et al., 2013). We have recently implicated lamina‐associated factors Hdac3 and Srf in age‐dependent dysregulation of lipid metabolism in the liver (Bochkis, Przybylski, Chen & Regev, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…S5 for an example). We therefore used an alternative approach and defined hypomethylated blocks through their association with lamina‐associated domains (LADs, Guelen et al ., 2008). However, we could not observe an age‐related decrease in the average methylation level of LAD‐associated probes in our dataset (Figs 2A and S5).…”
Section: Resultsmentioning
confidence: 99%
“…For visualization, β values of the probes within the identified blocks were averaged for young and old epidermis datasets and smoothed using a locally weighted regression approach. LAD association of Infinium 450k probes was determined using published datasets (Guelen et al ., 2008). …”
Section: Methodsmentioning
confidence: 99%
“…According to this hypothesis, the dissociation of OCT1 from the nuclear envelope has been shown to be associated with collagenase gene up-regulation during the cell-aging process (Imai et al, 1997). On the other hand, two recent genome-wide localization studies revealed that the association with nuclear lamina was mostly characterized by a repressive chromatin environment, devoid of active histone marks and RNA polymerase II binding activities (Pickersgill et al, 2006;Guelen et al, 2008). Of interest, one demonstrated SRY partner protein is KRAB-O, which by means of KAP-1 is able to recruit histone deacetylase and HP1 heterochromatin protein (Peng et al, 2009).…”
Section: Subcellular Localization Of the Proteinmentioning
confidence: 99%